Efficacy of Pyrotinib in HER2-Overexpressing Salivary Duct Carcinoma With Lung Metastasis: A Case Report - Zi-yan Yang; Zi-yan Yang; Zi-yan Yang; Jia-huan Huang; Jia-huan Huang; Bo Chen; Chun-wei Xu; Lei Lei; Lei Lei; Xiao-jia Wang; Xiao-jia Wang; Mei-yu Fang (Frontiers in Oncology, 2020)
Background: Salivary duct carcinoma (SDC), an aggressive and rare malignancy with poor prognosis, is mostly associated with the overexpression of the androgen receptor (AR) and human epidermal growth factor receptor 2 (HER2). However, limited data are available for the targeting of both HER2 and AR in advanced/metastatic SDC.Case Presentation: A 62-year-old man with advanced SDC accompanied by lung and lymph node metastasis showed disease progression after two lines of chemotherapy and endocrine therapy. Metastatic lesions from the lung biopsy were obtained, and immunohistochemistry (IHC) indicated the overexpression of AR and HER2 (3+). The patient was administered pyrotinib (a pan-ErbB receptor tyrosine kinase inhibitor) and bicalutamide (an androgen receptor antagonist) as a third-line treatment. During the ten months of follow-up, a durable partial response was achieved with this combination.Conclusions: This is the first clinical study to report the successful application of pyrotinib in a patient with advanced SDC. We recommend that pyrotinib and bicalutamide be used as salvage therapy for AR and HER2-positive advanced metastases in SDC, given the favorable response and clinical benefit.